PENGGUNAAN ALAT PERAGA MATERI RENTAN MATEMATIKA SEKOLAH DASAR - Susanti, Mathilda; Sardjana, A; Rosnawati, R (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2015)
Both the abstract mathematical concept and who are in the stage of operasional concrete thinking need teaching media to bridge the gap. Teaching media is one of the alternatives used by teachers in elementary schools. The objective of this research is to improve the learning mathematics quality by means of appropriate media.This is action research consists of three cycles. The subject of the research is 19 first grade students of SD Negeri Palbapang J Bantul Yogyakarta.The result shows that (1) using the appropriatte teaching media canimprove the students’ activity in learning mathematics. By using the teaching media, the teacher can be more creative in solving the students’ learning problems. (2) The main handicap in using teaching media in the learning and teaching process is time constraint, lacking of media and teachers capability creating and developing media. (3) The students’difficulty in learning mathematics can be solved by teaching using media. Key words: media, susceptible teaching material, mathematics